Public Perception and Consumption Rate of Water Spinach (Ipomoea aquatica) among Malaysian Adult Population: Basis for Future Human Health Risk Assessment - Wong, Koe Wei; Yap, Chee Kong; Rosimah, Nulit; Hishamuddin, Omar; Ahmad Zaharin, Aris (INTI International University, 2025)
Understanding the consumption rates of water spinach is vital for accurately assessing its impact on health and nutrition among various demographic groups in Malaysia. This research provides an updated exploration of water spinach consumption patterns and public attitudes across the country. The study was conducted using a self-administered online questionnaire distributed to Malaysian adults (aged 18 and above), resulting in 191 complete responses collected between May 2023 and March 2024. Consumption rate data, initially derived from the monthly frequency and serving size reported by participants, was converted into weight-based measurements (where 84g is the standard weight of a vegetable serve) and subsequently weighted by ethnicity to improve demographic representativeness. A recent public survey revealed that the average daily intake of water spinach stands at 69.26 grams overall, with distinct gender differences: males consume an average of 80.52 grams, while females consume 36.90 grams. These variations highlight how dietary habits may differ between men and women, possibly influenced by factors such as cultural preferences or lifestyle choices. Consumption rates also differ significantly across ethnic groups. The Malay ethnic group reported an average consumption of 74.44 grams (males at 93.20 grams and females at 38.67 grams), showing a notable gender gap. In contrast, the Chinese community exhibited lower and more uniform rates, with overall consumption at 25.76 grams (males at 25.35 grams, and females at 26.12 grams), suggesting minimal gender disparity. The Indian community, however, reported the highest rates, with an overall average of 156.56 grams (males at 136.60 grams, and females at 43.04 grams), indicating significant variation within the group. The survey further revealed that while Malaysians possess a general awareness of water spinach—commonly valued for its affordability and versatility in local cuisine—this understanding lacks depth. Many may not fully grasp its nutritional benefits, such as its rich iron and vitamin content, or the best preparation methods to preserve these qualities. To address this knowledge gap, educational initiatives are recommended. These could include public health campaigns, community workshops, and school programs, designed to enhance awareness of water spinach’s health benefits, safe handling practices, and optimal cooking techniques, ensuring consumers are well-informed about this staple vegetable.